Application of Electrochemical Impedance for Characterising Arrays of Bi2S3 Nanowires. (10th July 2015) - Kunakova, Gunta; Katkevics, Juris; Viksna, Arturs; Gertnere, Zanda; Varghese, Justin; Holmes, Justin D.; Erts, Donats
Abstract: Electrochemical Impedance Spectroscopy (EIS) was used to characterise the electrical properties of bismuth sulphide (Bi2 S3 ) nanowires (NWs) templated within anodic aluminium oxide (AAO) membranes. A specially engineered cell, with a nominal electrolyte volume of 0.1–0.2 ml, was used to hold and measure the electrochemical impedance of the fragile NW/AAO samples. An equivalent circuit model was developed to determine the filling density of nanowires within the porous templates. The EIS method can be utilised to probe the nanowire filling density in porous membranes over large sample areas, which is often unobtainable using electron microscopy and conductive atomic force microscopy techniques.